SURMA NODIR CHOKHE JAL': SOCIO-CULTURE OF SURMA BARAK - Sharma, Bubul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The village life of the region depicted in the Novel is Jagdishpur village of undivided Cachar district. This district has a special importance in terms of regional folk culture, the society of this region is formed based on the geographic environment, economy, education etc. of the region.The life-centered Novel 'Surma Nodir Chokhe Jal' depicts the fruits of real experience. The characters of this novel represent the village of Jagdishpur described in the novel. While describing the nature of Jagdishpur village and the life practices of the people, the novelist has presented various aspects of the folk culture of the region very well. We have noticed that being a major agricultural region, it is really surprising to think about the various stages of rice cultivation. Again through the songs, we noticed that the wedding songs that have been playing for a long time on various occasions are the bearers and bearers of their own traditional traditions. There is a variety of subject matter in the songs as well as a variety of style. There is a distinct language and expression of thought.